Pharmacological evidence of the use of Cannabidiol in the treatment of Parkinson's Disease (Research, Society and Development, 2023)
Parkinson's Disease (PD) is considered the second most prevalent pathology of a neurodegenerative order among the elderly, it essentially affects the substantia nigra of the central nervous system, it is characterized as a chronic and progressive disease due to its pathophysiology, which leads to the progressive death of dopaminergic neurons in the basal ganglia. The gold standard treatment, even today, is performed with the immediate precursor of dopamine, the drug Levodopa, however, the substance brings several adverse effects such as dyskinesia and chronic pain, in this sense, studies regarding Cannabiol as an adjuvant therapy have proved promising. This is a bibliographic review study with a descriptive and explanatory character, in which the data collected came from scientific review productions collected on the platforms ScieELO (Scientific Electronic Library Online), LILACS (Latin American and Caribbean Literature in Sciences Health), BVSMS (Virtual Health Library of the Ministry of Health) and Google Scholar. It aims to catalog scientific evidence regarding the use of cannabidiol in the treatment of Parkinson's disease. Although the use of cannabinoids for medicinal purposes has expanded in the last decade, their application in Parkinson's disease still lacks more robust evidence and studies. Its application in the management of chronic pain in patients living with PD is promising, however the evidence is still scarce.